2018
DOI: 10.1159/000492170
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Processing of Frequency Changes Reflected by the Acoustic Change Complex in Adult Cochlear Implant Users

Abstract: The purpose of this study was to examine neural substrates of frequency change detection in cochlear implant (CI) recipients using the acoustic change complex (ACC), a type of cortical auditory evoked potential elicited by acoustic changes in an ongoing stimulus. A psychoacoustic test and electroencephalographic recording were administered in 12 postlingually deafened adult CI users. The stimuli were pure tones containing different magnitudes of upward frequency changes. Results showed that the frequency chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…Numerous studies involving normal-hearing listeners have reported positive effects of music training on pitch perception. For instance, our group and other researchers have reported that musicians, who undergo years of music training, exhibit superior performance of pitch perception and better neurophysiological responses relative to non-musicians (Besson et al, 2007;Kraus et al, 2009;Itoh et al, 2012;Fuller et al, 2014;Brown et al, 2017;Liang et al, 2018). Such long-term music training may be expanded to the speech domain and positively affect speech perception in noise (Parbery-Clark et al, 2009;Baskent and Gaudrain, 2016).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Numerous studies involving normal-hearing listeners have reported positive effects of music training on pitch perception. For instance, our group and other researchers have reported that musicians, who undergo years of music training, exhibit superior performance of pitch perception and better neurophysiological responses relative to non-musicians (Besson et al, 2007;Kraus et al, 2009;Itoh et al, 2012;Fuller et al, 2014;Brown et al, 2017;Liang et al, 2018). Such long-term music training may be expanded to the speech domain and positively affect speech perception in noise (Parbery-Clark et al, 2009;Baskent and Gaudrain, 2016).…”
Section: Introductionmentioning
confidence: 81%
“…The advantage of averaging responses from multiple electrodes was that the variability in CI data could be reduced, as the final EEG waveforms include more trials (Roman et al, 2005). The wave peaks of the onset CAEP (N1 and P2 peaks) and ACC response (N1 and P2 peaks) were identified within their own latency ranges (approximately in 100-300 ms after tone onset for the onset CAEP and 600-800 ms after the tone onset for the ACC, respectively, see Liang et al, 2016Liang et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artifact removal effectiveness was assessed based on the phase characteristics of the measured response. We measured in addition to the 40-Hz eASSR, eASSRs to three additional frequencies (34,37, and 43 Hz) and with the same stimulation parameters as the 100% MD stimulus, i.e. stimulated at a maximum perceptual modulation depth (MD % = 100%) and loudness level.…”
Section: Artifact Removal Effectiveness For Measuring Assrsmentioning
confidence: 99%
“…Given the cortical origin of the ACC it can potentially function as a final detector of how well the TEMs are encoded in the neural signal. The ACC has been successfully used as an electrophysiological measure of gap detection 33 , frequency change detection 34 , and the eACC for electrode discrimination [35][36][37] in CI users. Furthermore, the eACC N1 amplitude shows a similar pattern as the temporal modulation transfer function of CI users 38 .…”
mentioning
confidence: 99%